A model to understand COVID-19 preventive behaviors in young adults: Health locus of control and pandemic-related fear. (December 2022) - Bianchi, Dora; Lonigro, Antonia; Norcia, Anna Di; Tata, Daniele Di; Pompili, Sara; Zammuto, Marta; Cannoni, Eleonora; Longobardi, Emiddia; Laghi, Fiorenzo
This study investigated COVID-19 preventive behaviors in young adults, exploring the predictive roles of health locus of control and pandemic fear. A sample of 188 Italian young adults (Mage  = 22.76, SDage   =  1.95 ; 85% girls) completed an anonymous online survey assessing preventive behaviors, health locus of control styles (i.e. internal, chance, powerful others), and two dimensions of pandemic fear. Fear for COVID-19 consequences—but not general fear for contagion—significantly predicted prevention behaviors, and it also moderated the relationships between each health locus of control style and preventive behaviors. Our findings have relevant implications for research and social policies.